UPAYA PENINGKATAN KETERAMPILAN KADER DENGAN COMMON COLD MASSAGE THERAPY DI WILAYAH KERJA PUSKESMAS GAMBIRSARI SURAKARTA - Siti Nurjanah; Erinda Nur Pratiwi; Ernawati Ernawati; Wijayanti Wijayanti (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2020)
Baby massage is a direct contact therapy with the body that can provide a feeling of security andcomfort to babies. Regular baby massage will increase catecholamine hormones (epinephrine andnorepinephrine) which can stimulate growth and development because they increase appetite, gainweight, and stimulate the development of brain structure and function. One of the massage therapy is the common cold massage therapy which is very effective for babies or children who have a common cold. After efforts to improve skills, it is expected that cadres in the Gambirsari Community Health Center work area can carry out common cold massage therapy as a teaching material for mothers in BKB (family development for toddlers). Implementation method with demonstration and discussion. The media used uses phantom babies, baby oil, LCD, laptop, and projector. The implementation of health education is carried out in posyandu activities, namely in September 2019-February2020 The matter of community service is that 90% of cadres can do the common cold massage therapy independently. As well as from the results of monitoring and evaluation by meeting again at the Tanggul Asri Posyandu, 90% of the cadres gave demonstrations of common cold massage therapy to mothers who had babies and toddlers. Based on the implementation of community service, it can be concluded that there is an increase in the knowledge and skills of cadres about common cold massage therapy at the Tanggul Asri Posyandu in the Gambirsari Community Health Center, Surakarta City.